Pengaruh Modifikasi Aktivitas Gerak Berbasis Permainan dalam Pembelajaran PJOK terhadap Kemampuan Motorik dan Motivasi Belajar Siswa - Aditya Harja Nenggar; Kahan Tony Hendrawan; Akbar Warisqianto; Arkavilla Richa Jannati Chusniah (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Based on the purpose of this study to determine the impact of the application of modified movement activities on motor skills and student learning motivation, the method with a quantitative approach with One group pretest - posttest design, the sample of this study were students of Budi Utomo Junior High School, grade VII students with 71 students with 36 male students and 35 female students, the sampling technique was purposive sampling Instruments for motor skills with motor ability tests, learning motivation using questionnaires Data Analysis In this study with descriptive analysis tests and also different tests. The results of the calculation of the results of the analysis of different tests with Paired Sample t-test, obtained a value (Sig. 2-tailed) 0.000 <0.05, so it can be understood that there is a significant difference that describes a positive impact on motor skills and student learning motivation. The conclusion can be understood that there is an influence of game-based movement activities on motor skills and learning motivation.